IMPLEMENTATION OF GENERAL PROVISIONS ON OCCUPATIONAL HEALTH AND SAFETY IN THE FACTORY ORDINANCE (NO. 45 OF 1942) (A QUALITATIVE STUDY) - Pallewaththa, P W K; Wijesiri, B M; Kumarasinghe, K K A H (PEOPLE: International Journal of Social Sciences, 2018)
In the late 1970s, Free Trade Zones were established in Sri Lanka as an important part of the economic development of the island. These zones were specially designated manufacturing areas which were set up to attract foreign investments to the country. In these places, occupational health and safety are vital features of the Human Resource Management. In the Sri Lankan context, studies regarding occupational health and safety are scarce. The general objective of this study was to explore the implementation of general provisions on occupational health, and safety in the Factory Ordinance (No. 45 of 1942) among workers in Katunayake Export Processing Zone. A qualitative approach was adapted to this study. The study consisted of two phases: in the first phase focus group discussion with workers were done, and in the second phase, ten in-depth interviews were conducted. Purposive sampling method was used to select participants from workers based on the inclusion criteria. Twenty workers (n=20) were selected from different factories in the zone. Saturation method was used as the guiding method of data collection. Data was analyzed using framework analysis. Study found that, implementation of general provisions on occupational health is remaining in a satisfactory level; implementing general provisions of occupational safety in work place is remaining at better status; however implementation of few provisions should be improved. A longitudinal study on occupational health and safety among factory workers and factory managers need to be conducted. In addition to that, improving awareness on Factories’ Ordinance (No. 45 of 1942) is recommended. Employers should also be empowered to intervene with managers for implementing general provisions and special provisions of occupational health and safety in the Factories’ Ordinance.